2011
DOI: 10.1111/j.1526-4637.2011.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Elective Courses for Medical Students: An Example in Pain

Abstract: Delivering the pain electives for medical students in an online format was an efficient educational method, with high student satisfaction scores. Medical educators should consider online electives for medical students in pain studies as well as in other content areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
0
20
0
7
Order By: Relevance
“…Answering the call for innovative education technologies to tackle the global challenge of pain management education (39), the next step of the research project has been to embed the identified themes in the design of an e-tool using virtual patient cases for medical undergraduate training, called the Pain Education e-Tool. It is a flexible, web-based program that may fit into crowded curricula because different parts of the cases and resources about pain could be referred to either by educators or by students on their own during their training (40). Currently under evaluation, the Pain Education e-Tool has been conceived and designed to provide students with the skills required to gather appropriate information about pain, to select therapeutic options from a wide spectrum not limited to pharmacological treatments and including interprofessional collaboration, to develop a mutual and trusting relationship with patients and, finally, to become aware of their own biases and prejudice toward patients with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Answering the call for innovative education technologies to tackle the global challenge of pain management education (39), the next step of the research project has been to embed the identified themes in the design of an e-tool using virtual patient cases for medical undergraduate training, called the Pain Education e-Tool. It is a flexible, web-based program that may fit into crowded curricula because different parts of the cases and resources about pain could be referred to either by educators or by students on their own during their training (40). Currently under evaluation, the Pain Education e-Tool has been conceived and designed to provide students with the skills required to gather appropriate information about pain, to select therapeutic options from a wide spectrum not limited to pharmacological treatments and including interprofessional collaboration, to develop a mutual and trusting relationship with patients and, finally, to become aware of their own biases and prejudice toward patients with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Nos estudos analisados, os usuários apontaram aspectos positivos do conteúdo e aparência das TICs, como: navegabilidade, clareza de informações, pertinência dos objetivos e conteúdo propostos, estética do layout, recursos audiovisuais, referências utilizadas, interatividade, carga horária, feedback, tutores e ajuda ao usuário. Puljak (19) Croácia 2011…”
Section: Resultsunclassified
“…As estratégias de educação mediadas por tecnologia constituem-se como alternativa ao ensino tradicional, visto que reúnem vantagens descritas nos estudos, tais como: flexibilidade temporal (15)(16)18,41,48) , desenvolvimento de autonomia e autoconfiança em relação ao aprendizado (31,(45)(46)(47)(48) , aplicação dos conhecimentos apreendidos no AVA na prática clínica (24) , estudo auto direcionado e centrado no usuário (27-46-18-48) , desenvolvimento de competências e conhecimentos a partir de experiências de aprendizagem ativa (29,35,43) , maior custo benefício para o treinamento de profissionais (19)(20)(21)(22)37,40) , ambiente motivador e engajador (20,45) , facilitação da comunicação entre os cursistas e professores/tutores (19) , ampliação de buscas rápidas por informações (19,48) e atualização rápida e constante de novas evidências científicas (16)(17)(18)(19)40) .…”
Section: Dor Pediátricaunclassified
See 1 more Smart Citation
“…These include online interactive modules, seminars and didactic teaching over a course of days or weeks, small group teaching, interactive conference series, inter-professional discussions, and use of standardized patients; application of these techniques has yielded mixed results. [36][37][38][39] One undergraduate medical education program in the US found that the integration of elements to strengthen emotional skills is an effective educational approach when teaching students about pain. 37 The investigators in this study reported that learners who used personal, reflective portfolios to build awareness of the affective dimensions of pain demonstrated attainment of foundation knowledge, robust engagement in tasks addressing emotional development, and high levels of learner satisfaction.…”
Section: Discussionmentioning
confidence: 99%